Binder for negative electrode of secondary battery, negative electrode of secondary battery, and secondary battery

A core-shell structured binder with an isoprene-based core and butadiene-based shell addresses volume changes in secondary battery electrodes, enhancing stability and lifespan by maintaining binding force and reducing electrolyte impregnation.

JP7612276B2Active Publication Date: 2025-01-14LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023522526
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-23
Filing Date
2021-10-20
Publication Date
2025-01-14
Estimated Expiration
2041-10-20

AI Technical Summary

Technical Problem

Secondary batteries face issues with stability and lifespan degradation due to volume changes in the negative electrode active material during charging and discharging, which are exacerbated by electrolyte impregnation, leading to a decrease in binding force between the negative electrode active material and the current collector.

Method used

A binder for the negative electrode with a core-shell structure is developed, comprising an isoprene-based core and a butadiene-based shell, which minimizes volume expansion and maintains binding force through continuous emulsion polymerization, ensuring excellent adhesive strength and stability.

Benefits of technology

The core-shell binder structure enhances the lifespan and stability of secondary batteries by suppressing volume expansion and maintaining binding force, resulting in improved energy density and capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612276000001
    Figure 0007612276000001
  • Figure 0007612276000002
    Figure 0007612276000002
  • Figure 0007612276000003
    Figure 0007612276000003
Patent Text Reader

Abstract

The present invention relates to a binder for a secondary battery negative electrode, a secondary battery negative electrode, and a secondary battery. Specifically, the present invention aims to minimize volume changes in the negative electrode and the secondary battery by improving the binder applied to the negative electrode of the secondary battery, thereby increasing the energy density and minimizing capacity loss.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Cross-reference to related applications This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0138513 filed on October 23, 2020, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a binder for a negative electrode of a secondary battery, a negative electrode of a secondary battery, and a secondary battery. [Background technology]

[0003] The fields in which secondary batteries are used are expanding from portable electronic devices to medium- and large-sized devices such as hybrid cars and electric cars.

[0004] The negative electrode of the secondary battery includes a current collector and a negative electrode active material layer, where the negative electrode active material layer includes a negative electrode active material and a binder.

[0005] Specifically, various types of carbon-based materials, including artificial and natural graphite and hard carbon, capable of inserting / desorbing lithium, are used as negative electrode active materials. In addition, research is being conducted on the use of silicon, tin, silicon-tin alloys, etc. as negative electrode active materials to increase discharge capacity.

[0006] However, secondary batteries have a problem in that their stability and lifespan decrease as they are repeatedly charged and discharged. Specifically, the volume of the negative electrode active material expands and contracts as the secondary battery is repeatedly charged and discharged, and in this process, the binding strength of the binder that binds the negative electrode active material to the current collector may decrease. This problem becomes more severe as the discharge capacity of the negative electrode active material increases.

[0007] Furthermore, in a secondary battery, the binder of the negative electrode may expand due to impregnation with the electrolyte, which may also reduce the binding strength of the binder.

[0008] Therefore, in order to realize a secondary battery with high capacity, high performance, and long life, it is necessary to minimize the volumetric changes of the negative electrode and the secondary battery. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention aims to minimize the volume change of the negative electrode and the secondary battery by improving the binder applied to the negative electrode of the secondary battery, thereby increasing the energy density and minimizing the capacity reduction. [Means for solving the problem]

[0010] Specifically, in one embodiment of the present invention, a binder for a negative electrode of a secondary battery is provided, which comprises binder particles having an isoprene-based core and a butadiene-based shell structure.

[0011] In another embodiment of the present invention, a method for producing a binder for a negative electrode of a secondary battery is provided, in which an isoprene-based core is synthesized, followed by the formation of a butadiene-based shell in a continuous process.

[0012] In still another embodiment of the present invention, there is provided a negative electrode mix, a negative electrode, and a secondary battery, each including the negative electrode binder of the above-described embodiment. Effect of the Invention

[0013] The negative electrode binder of the embodiment includes an isoprene-based core that has a low electrolyte impregnation rate and suppresses volume expansion, thereby improving the lifespan of a secondary battery; and a butadiene-based shell that has excellent adhesive strength and can maintain the binding strength between the negative electrode active material and the current collector even after repeated charging and discharging, thereby ultimately ensuring the stability and lifespan of the secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In the present invention, the terms "first", "second", etc. are used to describe various components, and the terms are used only to distinguish one component from another component.

[0015] In addition, the terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "includes", "has" or "has" are intended to specify the presence of an embodied feature, number, step, component, or combination thereof, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0016] As used herein, when a layer or element is referred to as being "on" or "on top of" another layer or element, this means that the layer or element is formed directly on the other layer or element, or that other layers or elements may be additionally formed between layers, on the object, or on the substrate.

[0017] Unless otherwise defined herein, "copolymer" may mean block copolymer, random copolymer, graft copolymer, or alternating copolymer, and "copolymer" may mean block copolymer, random copolymer, graft copolymer, or alternating copolymer.

[0018] Since the present invention can be modified in various ways and has various forms, specific examples will be illustrated and described in detail below. However, this is not intended to limit the present invention to the specific embodiments, and it should be understood that the present invention includes all modifications, equivalents, and alternatives within the spirit and technical scope of the present invention.

[0019] Binder for negative electrodes of secondary batteries In one embodiment of the present invention, a binder for a negative electrode of a secondary battery is provided, which comprises binder particles having a core-shell structure.

[0020] The binder for a negative electrode according to the embodiment may have both advantages of the core particles and advantages of the shell.

[0021] Specifically, the binder particles having a core-shell structure include a copolymer core particle including a repeating unit derived from an isoprene-based monomer; and a copolymer shell located on the surface of the core particle and including a repeating unit derived from a butadiene-based monomer.

[0022] This is because the secondary battery includes an isoprene-based core that has a low electrolyte impregnation rate and suppresses volume expansion, thereby improving the lifespan of the secondary battery; and a butadiene-based shell that has excellent adhesive strength and can maintain the binding strength between the negative electrode active material and the current collector even after repeated charging and discharging, thereby ultimately ensuring the stability and lifespan of the secondary battery.

[0023] The binder for the negative electrode according to the embodiment may be formed only from the binder particles having the core-shell structure, which are solid contents, or may be realized in the form of a composition to which an aqueous solvent or the like is added.

[0024] The negative electrode binder according to the embodiment will be described in detail below.

[0025] Core Particles The core particle may be a copolymer comprising (a) a first repeating unit derived from an isoprene-based first monomer, (b) a second repeating unit derived from an aromatic vinyl-based second monomer, and (c) a third repeating unit derived from an unsaturated carboxylic acid-based third monomer.

[0026] In the core particle, the first repeating unit is derived from an isoprene-based first monomer. Specifically, the first repeating unit corresponds to a structural unit of a copolymer formed from the isoprene-based first monomer supplied during the synthesis of the core particle.

[0027] When such a first repeating unit is contained in the core particle, the binder containing it is prevented from being impregnated with an electrolyte and from expanding in volume, thereby improving the life of the secondary battery.

[0028] Specifically, the first monomer may be isoprene.

[0029] In the core particle, the second repeating unit is derived from an aromatic vinyl second monomer. Specifically, the second repeating unit corresponds to a structural unit of a copolymer formed from the aromatic vinyl second monomer supplied during the synthesis of the core particle.

[0030] When the core particle contains such a second repeating unit, the binder containing the second repeating unit can have improved strength and affinity with the electrolyte.

[0031] Specifically, the aromatic vinyl second monomer may be at least one selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, 4-tert-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, and divinylbenzene, and may be, for example, styrene.

[0032] In the core particle, the third repeating unit is derived from an unsaturated carboxylic acid-based third monomer. Specifically, the third repeating unit corresponds to a structural unit of a copolymer formed from the third monomer supplied during the synthesis of the core particle.

[0033] When such a third repeating unit is contained in the core particle, the binder containing it can have improved strength, polymerization stability, and storage stability.

[0034] Specifically, the unsaturated carboxylic acid third monomer may be at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid, for example, acrylic acid and itaconic acid.

[0035] The total amount (100% by weight) of the core particle may contain (a) 30 to 65% by weight of a first repeating unit derived from an isoprene-based first monomer, (b) 30 to 65% by weight of a second repeating unit derived from an aromatic vinyl-based second monomer, and (c) 0.1 to 10% by weight of a third repeating unit derived from an unsaturated carboxylic acid-based third monomer.

[0036] Within such a range, the effects of the first repeating unit to the third repeating unit can be harmoniously achieved.

[0037] For example, in the total amount (100% by weight) of the core particle, (a) the first repeat unit derived from the isoprene-based first monomer may be contained in an amount of 30% by weight or more, 32% by weight or more, 34% by weight or more, or 36% by weight or more, and may be contained in an amount of 65% by weight or less, 62% by weight or less, 59% by weight or less, or 56% by weight or less.

[0038] In addition, in the total amount (100% by weight) of the core particle, (b) the second repeating unit derived from the aromatic vinyl second monomer may be contained in an amount of 30% by weight or more, 32% by weight or more, 34% by weight or more, or 36% by weight or more, and 65% by weight or less, 62% by weight or less, 59% by weight or less, or 56% by weight or less.

[0039] In addition, in the total amount (100% by weight) of the core particle, (c) the third repeating unit derived from an unsaturated carboxylic acid-based third monomer may be contained in an amount of 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, or 3% by weight or more, and may be contained in an amount of 10% by weight or less, 9% by weight or less, 8% by weight or less, or 7% by weight or less.

[0040] shell The shell may be a copolymer comprising (d) a fourth repeat unit derived from a butadiene-based fourth monomer, (e) a fifth repeat unit derived from an aromatic vinyl-based fifth monomer, and (f) a sixth repeat unit derived from an unsaturated carboxylic acid-based sixth monomer.

[0041] In the shell, the fourth repeating unit is derived from a butadiene-based fourth monomer. Specifically, the fourth repeating unit is derived from a butadiene-based fourth monomer provided during the synthesis of the core particle. butadiene It corresponds to a structural unit of a copolymer formed from a fourth monomer.

[0042] When such a fourth repeating unit is included in the shell, the binder including the fourth repeating unit has excellent adhesive strength and can maintain the binding strength between the negative electrode active material and the current collector even after repeated charging and discharging.

[0043] Specifically, the fourth monomer may be 1,3-butadiene.

[0044] In the shell, the fifth repeating unit is derived from an aromatic vinyl fifth monomer. Specifically, the fifth repeating unit corresponds to a structural unit of a copolymer formed from the aromatic vinyl fifth monomer supplied during the synthesis of the shell.

[0045] When such a fifth repeat unit is included in the shell, the binder containing it can have improved strength and affinity with the electrolyte.

[0046] Specifically, the aromatic vinyl fifth monomer may be at least one selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, 4-tert-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, and divinylbenzene, and may be, for example, styrene.

[0047] The above shellIn the particles, the sixth repeating unit is derived from an unsaturated carboxylic acid sixth monomer. shell It corresponds to the structural unit of the copolymer formed from the sixth monomer supplied during particle synthesis.

[0048] When such a sixth repeat unit is included in the shell, the binder containing it can have improved strength, polymerization stability, and storage stability.

[0049] Specifically, the unsaturated carboxylic acid sixth monomer may be at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid, for example, acrylic acid and itaconic acid.

[0050] The total amount (100% by weight) of the shell may contain (d) 30 to 85% by weight of a fourth repeating unit derived from a butadiene-based fourth monomer, (e) 10 to 65% by weight of a fifth repeating unit derived from an aromatic vinyl-based fifth monomer, and (f) 0.1 to 15% by weight of a sixth repeating unit derived from an unsaturated carboxylic acid-based sixth monomer.

[0051] Within such a range, the effects of the fourth to sixth repeating units can be harmonious.

[0052] For example, in the total amount (100% by weight) of the shell, (d) the fourth repeat unit derived from a butadiene-based fourth monomer may be contained in an amount of 30% by weight or more, 32% by weight or more, 34% by weight or more, or 36% by weight or more, and 85% by weight or less, 82% by weight or less, 78% by weight or less, or 75% by weight or less.

[0053] In addition, in the total amount (100% by weight) of the core particles, (e) a fifth monomer derived from an aromatic vinyl monomer 5 The repeating units may be present at 10% by weight or more, 12% by weight or more, 14% by weight or more, or 16% by weight or more, and at 65% by weight or less, 62% by weight or less, 59% by weight or less, or 56% by weight or less.

[0054] In addition, in the total amount (100% by weight) of the core particle, the sixth repeating unit derived from the unsaturated carboxylic acid-based sixth monomer may be contained in an amount of 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, or 3% by weight or more, and may be contained in an amount of 15% by weight or less, 13% by weight or less, 11% by weight or less, or 9% by weight or less.

[0055] Weight ratio of core particles and shell In the core-shell binder particles, the weight ratio of the core particle to the shell (core:shell) may be 1:1 to 15:1, specifically 2:1 to 14:1, more specifically 3:1 to 13:1, for example 4:1 to 12:1.

[0056] Within this range, the effects of the isoprene-based core, which can suppress volume expansion and improve the life of the secondary battery, and the butadiene-based shell, which has excellent adhesive strength and can maintain the binding strength between the negative electrode active material and the current collector even after repeated charging and discharging, can be balanced.

[0057] Average particle size of binder particles Meanwhile, the core-shell structured binder particles may be prepared through continuous emulsion polymerization and have a latex particle shape.

[0058] Specifically, the binder particles having the core-shell structure may be latex particles having an average particle size of 90 to 500 nm.

[0059] The average particle size of the latex particles can be measured using a particle size analyzer (NICOMP AW380, manufactured by PSS) using dynamic light scattering.

[0060] Specifically, in this specification, 'average particle size' refers to the arithmetic mean particle size in particle size distribution measured by dynamic light scattering. In this case, the arithmetic mean particle size can be measured as the intensity distribution mean particle size, the volume distribution mean particle size, or the number distribution mean particle size, among which it is preferable to measure it as the intensity distribution mean particle size.

[0061] For example, the core-shell structured binder particles may be latex particles having an average particle size of 90 nm or more, 120 nm or more, 150 nm or more, or 170 nm or more, but 500 nm or less, or 400 nm or less, or 300 nm or less, or 200 nm or less.

[0062] If the average particle size of the binder particles having the core-shell structure is too small, the viscosity may increase and the adhesive strength of the mixture layer containing the binder particles to the current collector may be weakened. Conversely, if the average particle size of the binder particles having the core-shell structure is too large, the stability of the particles may be reduced.

[0063] Aqueous Solvent In addition, the binder for a negative electrode according to the embodiment may be realized in the form of a latex composition by further including an aqueous solvent, i.e., water, together with the binder particles having the core-shell structure.

[0064] The aqueous solvent may be used in an amount of about 50 to about 1,000 parts by weight, specifically about 100 to about 400 parts by weight, based on 100 parts by weight of the binder particles having a core-shell structure, in terms of stability and viscosity control of the latex particles (the binder particles having the core-shell structure). For example, the aqueous solvent may be used so that the total solid content (TSC) of the binder for the negative electrode according to the embodiment is adjusted to about 10 to about 65% based on the total amount (100% by weight) of the binder.

[0065] If the amount of the aqueous solvent is too small, the stability of the latex particles (the binder particles having the core-shell structure) may decrease, whereas if the amount of the solvent is too large, the viscosity may decrease and the adhesive strength of the binder may weaken, resulting in a decrease in the overall performance of the battery.

[0066] Method for producing binder for negative electrode of secondary battery In another embodiment of the present invention, a method for producing a binder for a negative electrode of a secondary battery is provided, in which an isoprene-based core is synthesized, followed by the formation of a butadiene-based shell in a continuous process.

[0067] Specifically, the manufacturing method of the embodiment includes the steps of: polymerizing a first monomer mixture including an isoprene-based monomer to prepare copolymer core particles including a repeating unit derived from the isoprene-based monomer; and polymerizing a second monomer mixture including a butadiene-based monomer in the presence of the core particles to form a copolymer shell including a repeating unit derived from the butadiene-based monomer on a surface of the core particles, thereby obtaining the binder for a negative electrode of the embodiment.

[0068] The manufacturing method according to the embodiment will be described in detail below, and any description that overlaps with the above description will be omitted.

[0069] First monomer mixture By polymerizing the first monomer mixture, copolymer core particles containing repeating units derived from an isoprene-based monomer can be produced.

[0070] Specifically, the first monomer mixture may include (a) an isoprene-based first monomer, (b) an aromatic vinyl-based second monomer, and (c) an unsaturated carboxylic acid-based third monomer.

[0071] The content of each monomer in the first monomer mixture may be the same as the content of each repeating unit in the core particle, and a detailed description thereof will be omitted.

[0072] Second Monomer Mixture By polymerizing the second monomer mixture in the presence of the core particles, a copolymer shell containing repeat units derived from a butadiene-based monomer can be formed on the surface of the core particles.

[0073] Specifically, the second monomer mixture may include (d) a butadiene-based fourth monomer, (e) an aromatic vinyl-based fifth monomer, and (f) an unsaturated carboxylic acid-based sixth monomer.

[0074] The content of each monomer in the second monomer mixture may be the same as the content of each repeating unit in the shell, and a detailed description thereof will be omitted.

[0075] Emulsion Polymerization The polymerization of the first monomer mixture and the polymerization of the second monomer mixture can each be carried out independently by an emulsion polymerization method.

[0076] Specifically, each of the above steps may be carried out in the presence of an aqueous solvent, an emulsifier, and a polymerization initiator.

[0077] Also, in each step, emulsion polymerization can be carried out by single polymerization or multi-stage polymerization, where single polymerization means a method in which the monomers used are simultaneously polymerized in a single reactor, and multi-stage polymerization means a method in which the monomers used are sequentially polymerized in two or more stages.

[0078] The aqueous solvent is as described above, and therefore a detailed description thereof will be omitted.

[0079] The polymerization temperature and polymerization time of the emulsion polymerization for producing the copolymer can be appropriately determined depending on the case. For example, the polymerization temperature may be about 50° C. to about 200° C., and the polymerization time may be about 0.5 hours to about 20 hours.

[0080] Polymerization initiator The polymerization initiator usable in the emulsion polymerization may be an inorganic or organic peroxide. For example, a water-soluble initiator including potassium persulfate, sodium persulfate, ammonium persulfate, etc., and an oil-soluble initiator including cumene hydroperoxide, benzoyl peroxide, etc. may be used.

[0081] Activator In addition, an activator may be further included to promote the initiation of the peroxide reaction together with the polymerization initiator. As the activator, at least one selected from the group consisting of sodium formaldehyde sulfoxylate, sodium ethylenediaminetetraacetate, ferrous sulfate, and dextrose may be used.

[0082] emulsifier The emulsifier for the emulsion polymerization may be an anionic emulsifier such as sodium dodecyl diphenyl ether disulfonate, sodium lauryl sulfate, sodium dodecyl benzene sulfonate, or dioctyl sodium sulfosuccinate, or a nonionic emulsifier such as polyethylene oxide alkyl ether such as polyoxyethylene lauryl ether, polyethylene oxide alkyl aryl ether, polyethylene oxide alkyl amine, or polyethylene oxide alkyl ester. Such an emulsifier is a material having both a hydrophilic group and a hydrophobic group, and forms a micelle structure during the emulsion polymerization process, allowing the polymerization of each monomer to occur within the micelle structure. Preferably, the anionic emulsifier and the nonionic emulsifier may be used alone or in combination of two or more kinds, and it is more effective to use a mixture of an anionic emulsifier and a nonionic emulsifier, but the present invention is not necessarily limited to such a type of emulsifier.

[0083] The emulsifier can be used, for example, in an amount of about 0.01 to about 10 parts by weight, about 1 to about 10 parts by weight, or about 3 to about 5 parts by weight, per 100 parts by weight of the total monomer components used in the production of the copolymer.

[0084] Negative electrode mixture and negative electrode In still another embodiment of the present invention, there is provided a negative electrode mixture including the negative electrode binder of the above-described embodiment and a negative electrode active material, and there is provided a negative electrode including a negative electrode mixture layer including such a negative electrode mixture and a negative electrode current collector.

[0085] Except for the negative electrode binder of the embodiment, the negative electrode mixture, the negative electrode active material used in the negative electrode, the negative electrode current collector, etc. may each include commonly known components.

[0086] Negative electrode mixture The solid content of the negative electrode binder of the embodiment may be 1 wt% to 10 wt%, specifically 1 wt% to 5 wt%, based on the total weight (100 wt%) of the negative electrode mixture. When this is satisfied, the content of the negative electrode active material can be relatively increased, and the discharge capacity of the negative electrode can be further improved.

[0087] Meanwhile, the negative electrode binder according to the embodiment has excellent properties in terms of binding strength, mechanical properties, and the like. Therefore, even when a graphite-based negative electrode active material is used as the negative electrode active material of the negative electrode mixture, or even when a negative electrode active material having a higher capacity is used, the binder can maintain binding strength between the negative electrode active materials, between the negative electrode active material and the negative electrode current collector, and can suppress expansion of the negative electrode active material due to its own mechanical properties.

[0088] The negative electrode binder of the embodiment is suitable for use with not only graphite-based negative electrode active materials but also negative electrode active materials having higher capacities than graphite-based negative electrode active materials. Therefore, the type of the negative electrode active material is not particularly limited in the embodiment of the present invention.

[0089] Specifically, the negative electrode active material includes carbon such as non-graphitizable carbon and graphite-based carbon; Lix Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8, etc. metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. can be used.)

[0090] If necessary, a conductive material, a filler, etc. can be further added to the negative electrode binder of the above embodiment.

[0091] The conductive material is used to impart conductivity to the negative electrode, and any material can be used as long as it is an electron conductive material that does not cause a chemical change in the constructed battery. Examples thereof include carbon-based substances such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber; metal-based substances such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or a conductive material containing a mixture thereof can be used.

[0092] The filler is selectively used as a component for suppressing the expansion of the negative electrode, does not induce a chemical change in the battery, and is not particularly limited as long as it is a fibrous material. For example, olefin-based polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber can be used.

[0093] secondary battery In another embodiment of the present invention, a secondary battery is provided that includes the negative electrode of the above embodiment. Such a secondary battery may include a positive electrode, an electrolyte, and a negative electrode, and may be realized as a lithium secondary battery.

[0094] The lithium secondary battery may be manufactured by impregnating an electrode assembly including a positive electrode, a separator, and a negative electrode with a non-aqueous electrolyte.

[0095] negative electrode The negative electrode can be manufactured by applying the negative electrode mixture of the above-mentioned embodiment onto a negative electrode current collector, followed by drying and rolling.

[0096] The negative electrode current collector is generally manufactured to a thickness of 3 μm to 500 μm. Such a negative electrode current collector is not particularly limited as long as it is conductive without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface, and it can be used in various forms such as film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0097] positive electrode The positive electrode includes a positive electrode active material, which may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M xLithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li2Mn3MO8 (wherein M=Fe, Co, Ni, Cu or Zn); LiNi x Mn 2-x Examples of the lithium manganese oxide include, but are not limited to, lithium manganese composite oxides having a spinel structure represented by the formula LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.

[0098] The positive electrode current collector is generally manufactured to a thickness of 3 μm to 500 μm. Such a positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. The current collector can be formed with fine irregularities on its surface to increase the adhesive force of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0099] The conductive material is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskey such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0100] The positive electrode may use a commonly known binder, representative examples of which include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.

[0101] The negative electrode and the positive electrode can be manufactured by mixing an active material and a binder, and optionally a conductive material and a filler, in a solvent to prepare a slurry-phase electrode mixture, and then coating the electrode mixture on each electrode current collector. Such an electrode manufacturing method is widely known in the art, and therefore a detailed description thereof will be omitted here.

[0102] Separation membrane The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move, and may be any separator that is commonly used in lithium batteries. That is, a separator that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability may be used. For example, the separator may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a non-woven or woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may be used as a single layer or multi-layer structure.

[0103] In some cases, a gel polymer electrolyte may be coated on the separator to enhance the stability of the battery. Representative examples of such gel polymers include polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, etc.

[0104] However, when a solid electrolyte other than the non-aqueous electrolyte is used, the solid electrolyte can also serve as the separator.

[0105] Nonaqueous electrolyte The non-aqueous electrolyte may be a liquid electrolyte including a non-aqueous organic solvent and a lithium salt, the non-aqueous organic solvent acting as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0106] As the non-aqueous electrolyte, a non-aqueous electrolytic solution, an organic solid electrolyte, an inorganic solid electrolyte, or the like is used.

[0107] As the non-aqueous electrolyte, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydroxyfuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxene, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, and ethyl propionate can be used.

[0108] As the organic solid electrolyte, for example, polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociation groups, and the like can be used.

[0109] As the inorganic solid electrolyte, for example, nitrides, halides, and sulfates of Li such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2 can be used.

[0110] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte, and examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, lithium 4-phenylborate, etc. can be used.

[0111] In addition, for the purpose of improving charge / discharge characteristics, flame retardancy, etc., the electrolyte may contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride or ethylene trifluoride may be further added, carbon dioxide may be further added to improve high-temperature storage characteristics, or FEC (fluoro-ethylene carbonate), PRS (propene sultone), FPC (fluoro-propylene carbonate), etc. may be further added.

[0112] Purpose The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0113] Preferred examples are presented below for better understanding of the invention. However, the following examples are merely for illustrating the invention and are not intended to limit the invention. EXAMPLES

[0114] <Example> Example 1 (1) Preparation of binder composition for negative electrode To prepare the core-shell structured binder particles, the polymerization was carried out in two stages.

[0115] 1) First step: Preparation of isoprene-based core particles A first monomer mixture was prepared by adding (a) isoprene (200 parts by weight), (b) styrene (150 parts by weight), (c) acrylic acid and itaconic acid (26 parts by weight), sodium polyoxyethylene lauryl ether sulfate (2 parts by weight) as an emulsifier, and potassium persulfate (4 parts by weight) as a polymerization initiator to water as a solvent.

[0116] The first monomer mixture was heated to 75° C., and then polymerized for about 5 hours while maintaining the temperature at 75° C. to obtain a core composition containing isoprene-based core particles and water.

[0117] 2) Second stage: Formation of butadiene-based shell Specifically, (d) butadiene (59 parts by weight), (e) styrene (33 parts by weight), (f) acrylic acid and itaconic acid (8 parts by weight), sodium polyoxyethylene lauryl ether sulfate (0.6 parts by weight) as an emulsifier, and potassium persulfate (1.2 parts by weight) as a polymerization initiator were added to water as a solvent to prepare a second monomer mixture.

[0118] The second monomer mixture was added to the first binder composition in an amount such that the weight ratio of the first monomer mixture:second monomer mixture was 9:1.

[0119] Thereafter, a polymerization reaction was carried out for about 5 hours while maintaining the temperature at 75° C., and finally a binder composition containing water and binder (latex) particles including isoprene-based core particles and butadiene-based shells was obtained.

[0120] (2) Preparation of negative electrode mixture composition Artificial graphite (95 parts by weight) was used as the negative electrode active material, acetylene black (1.5 parts by weight) was used as the conductive material, the binder composition of Example 1 (2.0 parts by weight, of which the solid content was 40% by weight), and carboxymethyl cellulose (1.5 parts by weight) was used as the thickener, and these were mixed by stirring in water as the dispersion medium for 1 hour. At this time, the slurry phase was adjusted so that the total solid content was 50% by weight, and the negative electrode mixture composition of Example 1 was obtained.

[0121] (3) Manufacturing of negative electrodes A copper foil having a thickness of 10 μm was prepared as a negative electrode current collector. The negative electrode mixture composition of Example 1 was applied to the negative electrode current collector in an amount of 8.0 mg / cm2 per surface using a comma coater. 2 The mixture was dried in an oven at 80° C. for 10 minutes with hot air, and then roll-pressed to a total thickness of 190 μm to obtain a negative electrode of Example 1.

[0122] (4) Manufacture of secondary batteries Li as the positive electrode active material 1.03 Ni 0.6 Co 0.6 Mn 0.2 90 parts by weight of O2, 5.0 parts by weight of acetylene black as a conductive material, and 50 parts by weight of polyvinylidene fluoride (PVdF) as a binder (10% solid content) were mixed by stirring in NMP as a solvent for 1 hour. At this time, the slurry phase was adjusted so that the total solid content was 70% by weight, and a positive electrode mixture composition of Example 1 was obtained.

[0123] An aluminum foil having a thickness of 20 μm was prepared as a positive electrode current collector. The positive electrode mixture composition of Example 1 was applied to the negative electrode current collector in an amount of 15.6 mg / cm per surface using a comma coater. 2 The mixture was dried in an oven at 80° C. for 10 minutes with hot air, and then roll-pressed to a total thickness of 190 μm to obtain a positive electrode of Example 1.

[0124] A separator was inserted between the negative electrode and the positive electrode of Example 1, and the resulting assembly was followed by injecting an electrolyte solution to complete a lithium ion battery according to a method commonly known in the art.

[0125] The electrolyte used was prepared by dissolving LiPF6 in a mixed solvent of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) (weight ratio of EC:PC:DEC=3:2:5) to a concentration of 1.3M, and adding fluoroethylene carbonate (FEC) to the electrolyte to account for 10% by weight of the total weight.

[0126] Example 2 The negative electrode binder composition, the negative electrode mixture composition, the negative electrode, and the secondary battery of Example 2 were manufactured in the same manner as in Example 1, except that the weight ratio of the first monomer mixture and the second monomer mixture was changed.

[0127] Specifically, in Example 2, the composition of the first monomer mixture and the composition of the second monomer mixture were the same, but the weight ratio of the first monomer mixture:the second monomer mixture was changed to 6:1.

[0128] Example 3 The negative electrode binder composition, the negative electrode mixture composition, the negative electrode, and the secondary battery of Example 3 were manufactured in the same manner as in Example 1, except that the weight ratio of the first monomer mixture and the second monomer mixture was changed.

[0129] Specifically, in Example 3, the composition of the first monomer mixture and the composition of the second monomer mixture were the same, but the weight ratio of the first monomer mixture:the second monomer mixture was changed to 4.5:1.

[0130] Example 4 The negative electrode binder composition, the negative electrode mixture composition, the negative electrode, and the secondary battery of Example 4 were produced in the same manner as in Example 1, except that the compounding ratio of the first monomer mixture was changed.

[0131] Specifically, in Example 4, the composition of the second monomer mixture and the weight ratio of the first monomer mixture:second monomer mixture were the same, and when preparing the first monomer mixture, (a) isoprene (150 parts by weight), (b) styrene (200 parts by weight), and (c) acrylic acid and itaconic acid (26 parts by weight) were used.

[0132] Example 5 The negative electrode binder composition, the negative electrode mixture composition, the negative electrode, and the secondary battery of Example 5 were produced in the same manner as in Example 1, except that the compounding ratio of the first monomer mixture was changed.

[0133] Specifically, in Example 5, the composition of the second monomer mixture and the weight ratio of the first monomer mixture:second monomer mixture were the same, and when preparing the first monomer mixture, (a) isoprene (250 parts by weight), (b) styrene (200 parts by weight), and (c) acrylic acid and itaconic acid (26 parts by weight) were used.

[0134] Example 6 The negative electrode binder composition, the negative electrode mixture composition, the negative electrode, and the secondary battery of Example 6 were produced in the same manner as in Example 1, except that the compounding ratio of the second monomer mixture was changed.

[0135] Specifically, in Example 6, the composition of the first monomer mixture and the weight ratio of the first monomer mixture:second monomer mixture were the same, and when preparing the second monomer mixture, (d) butadiene (40 parts by weight), (e) styrene (52 parts by weight), and (f) acrylic acid and itaconic acid (8 parts by weight) were used.

[0136] Example 7 The negative electrode binder composition, the negative electrode mixture composition, the negative electrode, and the secondary battery of Example 7 were produced in the same manner as in Example 1, except that the compounding ratio of the second monomer mixture was changed.

[0137] Specifically, in Example 7, the composition of the first monomer mixture and the weight ratio of the first monomer mixture:second monomer mixture were the same, and when preparing the second monomer mixture, (d) butadiene (72 parts by weight), (e) styrene (20 parts by weight), and (f) acrylic acid and itaconic acid (8 parts by weight) were used.

[0138] Comparative Example 1 Only the first step of Example 1 was carried out to prepare a composition containing isoprene-based latex particles and water, which was used as a binder composition for a negative electrode of Comparative Example 1.

[0139] A negative electrode mixture composition, a negative electrode, and a secondary battery of Comparative Example 1 were produced in the same manner as in Example 1, except that the binder composition for the negative electrode was changed.

[0140] Comparative Example 2 The first step of Example 1 was omitted and only the second step was carried out to prepare a composition containing butadiene-based latex particles and water, which was used as a binder composition for a negative electrode of Comparative Example 2.

[0141] A negative electrode mixture composition, a negative electrode, and a secondary battery of Comparative Example 2 were produced in the same manner as in Example 1, except that the binder composition for the negative electrode was changed.

[0142] Comparative Example 3 The second monomer mixture of Example 1 was used to prepare the core particles, and the first monomer mixture of Example 1 was used to form the shell. A composition containing latex particles including butadiene-based core particles and isoprene-based shells, and water was prepared, and this composition was used as the negative electrode binder composition of Comparative Example 3.

[0143] A negative electrode mixture composition, a negative electrode, and a secondary battery of Comparative Example 3 were produced in the same manner as in Example 1, except that the binder composition for the negative electrode was changed.

[0144] Comparative Example 4 The second monomer mixture of Example 1 was used to prepare the core particles, and the second monomer mixture of Example 1 was also used to form the shell, to prepare a composition containing latex particles including butadiene-based core particles and butadiene-based shells, and water, which was used as the negative electrode binder composition of Comparative Example 4.

[0145] A negative electrode mixture composition, a negative electrode, and a secondary battery of Comparative Example 4 were produced in the same manner as in Example 1, except that the binder composition for the negative electrode was changed.

[0146] Comparative Example 5 The first monomer mixture of Example 1 was used to prepare the core particles, and the first monomer mixture of Example 1 was also used to form the shell, to prepare a composition containing latex particles including isoprene-based core particles and isoprene-based shells, and water. This composition was used as Comparative Example. 5 The binder composition for the negative electrode was used.

[0147] A comparative example was prepared in the same manner as in Example 1, except that the binder composition for the negative electrode was changed. 5 The negative electrode mixture composition, the negative electrode, and the secondary battery were manufactured.

[0148] For Examples 1 to 4 and Comparative Examples 1 to 5, the composition of the monomer mixture used in producing the core, the composition of the monomer mixture used in forming the shell, and the weight ratio of the core monomer mixture and the shell monomer mixture are summarized in Table 1 below.

[0149] [Table 1]

[0150] Experimental Example 1 The binder compositions of Examples 1 to 7 and Comparative Examples 1 to 5 were evaluated by the following methods, and the results are shown in Table 2 below.

[0151] 1) The binder may have a latex particle form produced through emulsion polymerization. The latex particles were measured using a particle size analyzer (NICOMP AW380, manufactured by PSS) to determine the arithmetic mean particle size of the binder particles in the binder composition, specifically the intensity distribution mean particle size.

[0152] 2) In the case of the viscosity of the latex, a Brookfield viscometer LV type and spindle #1 were used, and the viscosity value was stable after 1 minute or more at 70 rpm.

[0153] [Table 2]

[0154] The negative electrodes and secondary batteries of Examples 1 to 7 and Comparative Examples 1 and 2 were evaluated under the following conditions, and the results were recorded in Table 3 below.

[0155] (1) Negative electrode adhesive strength: After measuring the peel strength for each negative electrode of the examples and comparative examples at least five times, the average value was calculated and the average values ​​are shown in the table below. 3 The peel strength was measured by measuring the force (N) required to peel off a 10 mm wide adhesive tape from the negative electrode at a peel angle of 180° using a tensile tester (TA-XT, Stable Micro System).

[0156] (2) Measurement of electrolyte swelling (electrolyte uptake) The swelling degree of the binder in the electrolyte was measured. The binder dispersed in the solvent was applied to a PET film with a certain thickness and dried at 80°C for 24 hours or more, and the binder film was cut into a 1.5cm x 8cm specimen. The prepared specimen was immersed in the electrolyte for 24 hours, and the weights before and after immersion in the electrolyte were measured, and the binder weight change rate was evaluated according to the following [Equation 1].

[0157] The electrolyte used here had the same composition as that used in the manufacture of each lithium ion battery. [Formula 1] Electrolyte Uptake(%)=100×[Weight after immersion in electrolyte] / [Weight before immersion in electrolyte]

[0158] (3) Capacity retention rate of secondary battery after 300 cycles: In a thermostatic chamber at 25°C, each lithium secondary battery was charged in CC / CV mode with a charge / discharge current density of 1C until the battery voltage reached 4.3V, and then discharged in CC mode until the battery voltage reached 2.5V (one cycle), with a 20-minute rest period between the charge and discharge. A total of 300 cycles were performed. The ratio of the discharge capacity measured in the 300th cycle to the discharge capacity measured in the first cycle was calculated.

[0159] [Table 3]

[0160] It can be seen from Table 3 above that, compared with Comparative Examples 1 to 5, Examples 1 to 7 are all superior in negative electrode adhesive strength, electrolyte impregnation rate, and capacity retention rate after 300 cycles.

[0161] Specifically, in Comparative Example 1 in which isoprene-based particles were used as a binder, the weight change before and after immersion in the electrolyte was small, but it was confirmed that the initial adhesive strength of the negative electrode was only 12.2 gf / cm.

[0162] Comparative Example 5, in which latex particles comprising an isoprene-based core particle and an isoprene-based shell were used as the binder, also showed similar results to Comparative Example 1, in which isoprene-based particles were used as the binder.

[0163] In relation to this, it is presumed that although the isoprene-based latex particles can suppress electrolyte impregnation, they are insufficient in strengthening the initial adhesive strength of the negative electrode, which induces detachment of the negative electrode during long-term operation of the secondary battery, thereby negatively affecting cycle characteristics.

[0164] In Comparative Example 2, in which butadiene-based latex particles were used as the binder, the initial adhesive strength of the negative electrode was ensured, but it was confirmed that the weight change before and after immersion in the electrolyte was significant at 125%.

[0165] Comparative Example 4, in which latex particles comprising butadiene-based core particles and a butadiene-based shell were used as the binder, also showed similar results to Comparative Example 2, in which butadiene-based latex particles were used as the binder.

[0166] In the laboratory scale, the battery was evaluated up to 300 cycles, but if it is operated for a long period of time beyond this, the butadiene-based particles impregnated with the electrolyte will further lose their binding strength to the negative active material due to the contraction and expansion of the negative active material, which is predicted to hinder the cycle characteristics of the secondary battery.

[0167] On the other hand, in Comparative Example 3, in which latex particles containing butadiene-based core particles and isoprene-based shells were used as a binder, the initial adhesive strength of the negative electrode was partially improved compared to Comparative Example 1, and the weight change before and after immersion in the electrolyte remained at a level partially improved compared to Comparative Example 2.

[0168] In contrast, in the case of Examples 1 to 7 in which latex particles containing isoprene-based core particles and butadiene-based shells were used as binders, it was confirmed that an initial adhesive strength of 18 gf / cm or more was ensured, while the electrolyte impregnation rate was kept at a level of 115% or less, and a capacity retention rate of 88% or more after 300 cycles was ensured.

[0169] In this regard, it is understood that all of these advantages can be obtained by using isoprene-based latex particles that suppress electrolyte impregnation as a core and forming a butadiene-based shell with excellent adhesive strength on the surface.

[0170] By controlling the composition of the core (first monomer mixture), the composition of the shell (second monomer mixture), and the weight ratio of the core:shell (first monomer mixture:second monomer mixture) with reference to the examples 1 to 7 in addition to the description of the above embodiment, it is also possible to adjust the initial adhesion and impregnation rate of the negative electrode, as well as the life of the secondary battery, to within the desired range.

Claims

1. Contains binder particles having a core-shell structure, The binder particle having a core-shell structure includes a copolymer core particle including a repeating unit derived from an isoprene-based monomer; and a copolymer shell located on the surface of the core particle and including a repeating unit derived from a butadiene-based monomer; In the total amount (100% by weight) of the core particles, (a) 30 to 65% by weight of a first repeating unit derived from an isoprene-based first monomer; (b) 30 to 65% by weight of a second repeat unit derived from an aromatic vinyl second monomer, and (c) containing 0.1 to 10% by weight of a third repeating unit derived from an unsaturated carboxylic acid-based third monomer; In the total amount (100% by weight) of the shell, (d) 30 to 85% by weight of a fourth repeating unit derived from a butadiene-based fourth monomer; (e) 10 to 65% by weight of a fifth repeating unit derived from an aromatic vinyl fifth monomer, and (f) A binder for a negative electrode of a secondary battery, comprising 0.1 to 15% by weight of a sixth repeating unit derived from an unsaturated carboxylic acid-based sixth monomer.

2. 2. The binder for a negative electrode of a secondary battery according to claim 1, wherein the second monomer is at least one selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, 4-tert-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, and divinylbenzene.

3. 3. The binder for a negative electrode of a secondary battery according to claim 1, wherein the third monomer is at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid.

4. 4. The binder for a negative electrode of a secondary battery according to claim 1, wherein the fifth monomer is at least one selected from the group consisting of styrene, α-methylstyrene, β-methylstyrene, 4-tert-butylstyrene, chlorostyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, hydroxymethylstyrene, and divinylbenzene.

5. The binder for a negative electrode of a secondary battery according to any one of claims 1 to 4, wherein the sixth monomer is at least one selected from the group consisting of acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaric acid, itaconic acid, tetrahydrophthalic acid, crotonic acid, isocrotonic acid, and nadic acid.

6. The binder for a negative electrode of a secondary battery according to any one of claims 1 to 5, wherein a weight ratio of the core particles to the shell (core:shell) is 1:1 to 15:

1.

7. 7. The binder for a negative electrode of a secondary battery according to claim 1, wherein the binder particles having a core-shell structure are latex particles having an average particle size of 90 to 500 nm.

8. The binder for a negative electrode of a secondary battery according to any one of claims 1 to 7, further comprising an aqueous solvent.

9. 9. The binder for a negative electrode of a secondary battery according to claim 8, wherein the aqueous solvent is contained in an amount of 50 to 1,000 parts by weight based on 100 parts by weight of the binder particles having a core-shell structure.

10. polymerizing a first monomer mixture including an isoprene-based monomer to produce a copolymer core particle including repeat units derived from an isoprene-based monomer; and forming a copolymer shell including a repeating unit derived from the butadiene-based monomer on a surface of the core particle by polymerizing a second monomer mixture including a butadiene-based monomer in the presence of the core particle, In the total amount (100% by weight) of the core particles, (a) 30 to 65% by weight of a first repeating unit derived from an isoprene-based first monomer; (b) 30 to 65% by weight of a second repeat unit derived from an aromatic vinyl second monomer, and (c) containing 0.1 to 10% by weight of a third repeating unit derived from an unsaturated carboxylic acid-based third monomer; In the total amount (100% by weight) of the shell, (d) 30 to 85% by weight of a fourth repeating unit derived from a butadiene-based fourth monomer; (e) 10 to 65% by weight of a fifth repeating unit derived from an aromatic vinyl fifth monomer, and (f) The method includes 0.1 to 15% by weight of a sixth repeating unit derived from an unsaturated carboxylic acid sixth monomer.

11. 11. The method for producing a binder for a negative electrode of a secondary battery according to claim 10, wherein the first monomer mixture comprises (a) an isoprene-based first monomer, (b) an aromatic vinyl-based second monomer, and (c) an unsaturated carboxylic acid-based third monomer.

12. 12. The method for producing a binder for a negative electrode of a secondary battery according to claim 10 or 11, wherein the second monomer mixture contains (d) a butadiene-based fourth monomer, (e) an aromatic vinyl-based fifth monomer, and (f) an unsaturated carboxylic acid-based sixth monomer.

13. The method for producing a binder for a negative electrode of a secondary battery according to any one of claims 10 to 12, wherein the polymerization of the first monomer mixture and the polymerization of the second monomer mixture are each independently carried out in the presence of an aqueous solvent, an emulsifier, and a polymerization initiator.

14. The binder for a negative electrode of a secondary battery according to any one of claims 1 to 9; and a negative electrode active material;

15. A negative electrode mixture layer comprising the negative electrode mixture according to claim 14; and A negative electrode of a secondary battery comprising: a negative electrode current collector.

16. The negative electrode of claim 15 ; a positive electrode; and an electrolyte.

Citation Information

Patent Citations

  • Core-shell structured binders for use of anode materials of lithium ion secondary battery and method for preparing using the same, and slurry comprising said binders

    KR101698745B1

  • Negative electrode slurry composition, lithium ion secondary cell negative electrode, and lithium ion secondary cell

    WO2013183717A1

  • Binder composition for non-aqueous secondary battery, production method for binder composition for non-aqueous secondary battery, slurry composition for non-aqueous secondary battery electrode, electrode for non-aqueous secondary battery, and non-aqueous secondary battery

    WO2019172281A1